Dystopia Marketing From Dystopia to Transandalist Marketing for a Better Future - Yıldırım, Yusuf Ozan (Sakarya Üniversitesi Yayınları, 2025)
The future is often portrayed as a place of hope and progress. Yet, when we look at the present where algorithms shape our decisions, emotions, and identities, that vision seems increasingly distant. If the current trajectory continues, the future may resemble a dystopia more than the ideal we’ve been promised. In a world where marketing has helped design this reality, perhaps marketing can also help us rethink it. This book introduces Transandalist Marketing as a society-oriented approach that encourages reflection, responsibility, and renewal. It does not offer definitive solutions, but it asks a question worth considering: If marketing is society-oriented, why haven’t we become a better society?